3D‐Printed Multilayered Reinforced Material System for Gas Supply in CubeSats and Small Satellites. Issue 11 (3rd September 2019) - Singhal, Nimesh; Levchenko, Igor; Huang, Shiyong; Xu, Luxiang; Potrivitu, George-Cristian; Cherkun, Oleksii; Fang, Jinghua; Bazaka, Kateryna; Xu, Shuyan
Abstract : Further development of the near‐Earth satellite infrastructure as well as plans for colonization of the Moon and Mars require innovative materials and technologies to produce efficient space assets capable of active functioning for several years. Therefore, the development of compact and efficient devices has bloomed exponentially. Critical components of such devices, propulsion systems that include thrusters, and feed and power systems, have to be efficient and compact. Moreover, these systems shall be simple and cheap, to satisfy the need for thousands of small satellites planned to be launched in the near future. Herein, the design of a 3D‐printed, reinforced multilayered material system for gas supply to be used in CubeSats and small satellites of a 1U (10 × 10 × 11.3 cm) form factor is described. The main objective of the system is to provide 0.1 standard cubic centimeter per minute (sccm) of propellant to the thruster. To achieve that, a material system is designed for a propellant tank of ≈50 × 100 mm. Abstract : The design of a 3D‐printed multilayered material system for propellant storage and feed system, for a Hall thruster to be used in CubeSats and small satellites, is described. A 3D‐printed reinforced acrylonitrile butadiene styrene (ABS) tank is produced and tested as a proof of concept. Post‐processing techniques are used to reduce the tank leakage and enhance the strength.